Automation of a tertiary hospital pharmacy drug dispensing system in a lower-middle-income country: A case study and preliminary results - Ângela Maria Bagattini, PhDc; José Luiz Alvim Borges; Rachel Riera, PhD; Débora Cecília Mantovani Faustino de Carvalho (Elsevier, 2022)
Background: An increase in the use of automated systems has optimised the drug dispensing process in hospitals. Methods: This case study describes the implementation of automated drug dispensing system and presents the preliminary results of automated pharmaceutical dispensing with robots (PillPick® and BoxPicker®, ©Swisslog Healthcare) at Hospital Sírio-Libanês, a private tertiary hospital in Brazil. Results: During the study period, between 2013 (pre-automation) and 2017 (post-automation) the number total of medication errors has not changed post-automation, but there was significant reduction in error in the dispensing phase with a relative risk of 0.84 (95% confidence interval: 0.70-0.99) withal a reduction in the numbers of returned items, breakages, and loss of medications, although that delivery times have increased.. Conclusion: The study results suggest that the use of robotic systems in the central pharmacy may improve hospital pharmacy management and generate only a few errors in dispensing pharmaceuticals.